COMPARATIVE BIOACTIVITY OF PLANT EXTRACTS AND SYNTHETIC INSECT GROWTH REGULATORS AGAINST Spodoptera litura (F.) (LEPIDOPTERA: NOCTUIDAE) - Hasibuan, Rosma; Purnomo, Purnomo; Wibowo, Lestari; Izzaturrijal, Izzaturrijal; Lumbanraja, Jamalam (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Laboratory bioassays were conducted to compare the effects of the leaf extract of Acalypha indica L. (Euphorbiaceae) with synthetic insect growth regulators (IGRs) triflumuron and buprofezin against Spodoptera litura (F.). The experiment was set up as a randomized complete block design (RCBD). The treatments were two concentrations of A. indica extracts 1000 and 2000 ppm, two concentrations of buprofezin 100 and 200 ppm, two concentrations of triflumuron 120 and 240 ppm and control. Each treatment was replicated three times. Second instar larva of S. litura were used for the bioassays. Mortality and biological variables of treated and control larvae were recorded daily. The results indicated that the application of A. indica extracts and synthetic IGRs (buprofezin & triflumuron) significantly caused the S. litura mortality throughout the experimental period. At first, the toxicity of triflumuron on larval S. litura was significantly higher compared to those of buprofezin and Acalypha indica leaf extract. However, at the end of experimental period all treatments caused high mortality on S. litura, and those all were significantly different from control. The treatments also caused abnorrmal growth in larval, pupal, and adult stages. While in the control, larvae molted into normal adults. The results indicated that the use of biorational control agents such as synthetic insect growth regulators (IGRs) and those based on naturally derived products such as botanical insecticides show promise as a potential tool in S. litura management programs.